Politik, Adat, dan Tata Kelola Pangan: Kebijakan dan Nilai-Nilai Agama Patuntung dalam Mengantisipasi Krisis Pangan Suku Kajang - A. Muh. Rifky Nugraha; Abu Bakar (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2025)
Abstract. This article aims to reveal how the politics of food governance by looking at government policies and the implementation of Pantuntung religious values in anticipating the food crisis for the Kajang indigenous community in Bulukumba, Indonesia. This article borrows the concept of food security as an analytical tool and is described in a qualitativedescriptive manner with a data base based on field research. In general, this article concludes as follows; Firstly, the Regional Government of Bulukumba Regency issued Re-gional Regulation No. 9/2015 on the Inauguration, Recognition of Rights, and Protection of the Ammatoa Kajang Customary Law Community which explicitly guarantees the management and utilisation of land for the Kajang indigenous people individually and communally. Secondly, the indigenous people of the Kajang tribe protect their environment by being guided by Pasang in the Patuntung belief system. Thirdly, the culture of the Kajang indigenous people to ensure the availability of food to avoid a food crisis is to equip each of their houses with para'. Para' functions as a food governance mechanism adopted from the local wisdom of the Kajang tribe.